2019
DOI: 10.1175/jas-d-18-0194.1
|View full text |Cite
|
Sign up to set email alerts
|

Power-Law Scaling in the Internal Variability of Cumulus Cloud Size Distributions due to Subsampling and Spatial Organization

Abstract: In this study, the spatial structure of cumulus cloud populations is investigated using three-dimensional snapshots from large-domain LES experiments. The aim is to understand and quantify the internal variability in cloud size distributions due to subsampling effects and spatial organization. A set of idealized shallow cumulus cases is selected with varying degrees of spatial organization, including a slowly organizing marine precipitating case and five more quickly organizing diurnal cases over land. A subdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…Our study confirms this hypothesis, with the addition that tracking objects in time can give valuable information on the tendency of convection to form clusters. Another possible improvement could be new indices that take into account both ends of the size distribution function separately: Neggers et al (2019) have shown that spatial organization affects both ends of the cloud size PDF, but in different ways: while the number of large clouds increases, there is an enhanced variability in the number of small clouds, especially shallow cumulus clouds below the 1 km scale. However, in our study, we are mainly concerned with deep precipitating convection where such small cloud sizes are neglected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study confirms this hypothesis, with the addition that tracking objects in time can give valuable information on the tendency of convection to form clusters. Another possible improvement could be new indices that take into account both ends of the size distribution function separately: Neggers et al (2019) have shown that spatial organization affects both ends of the cloud size PDF, but in different ways: while the number of large clouds increases, there is an enhanced variability in the number of small clouds, especially shallow cumulus clouds below the 1 km scale. However, in our study, we are mainly concerned with deep precipitating convection where such small cloud sizes are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike SCAI and COP, which mainly quantify the degree of clustering, the NN-based organization index I org (Tompkins and Semie, 2017) is able to distinguish between three types of spatial distribution: clustered, regular, and random. In this approach, we treat objects as discs (similar to Nair et al, 1998), and we compute the cumulative distribution function of the NN edge-to-edge distances (NNCDF) and compare it to the NNCDF of theoretical randomly distributed objects over the same domain. The theoretical NNCDF is approximated by bootstrapping, in which a random number of objects with the observed size distribution are randomly placed over the domain (Weger et al, 1992;Nair et al, 1998).…”
Section: Indices Of Convective Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite observations (e.g., Zhao and Di Girolamo, 2007) and LES studies (e.g., Neggers et al, 2003) have shown that in shallow-cumulus cloud fields, the vast majority of clouds are small, and larger clouds are few and far-between. The cloud-size distribution has been variously characterized by lognormal, exponential, or power-law functions (e.g., Neggers et al, 2019). The R eff distributions at the cloud-layer midpoints for the layer-depth sensitivity experiments of Sect.…”
Section: Refereementioning
confidence: 99%